Enhanced Microgrid Reliability Through Optimal Battery Energy Storage System Type and Sizing - Mohammadreza Gholami (17032317) (2023)
Reliability plays a crucial role in the design and implementation of microgrids (MGs). The integration of battery energy storage systems (BESSs) with renewable energies has been proposed as a solution to enhance reliability. However, it is important to consider the type of BESS during integration to avoid overly optimistic evaluations of reliability and cost analysis in MGs. This paper aims to address this issue by finding the optimal size and type of BESS for improving the reliability of a MG. Several factors of the BESS, such as rated power, power cost, discharge time, efficiency, and life cycle, are considered based on the type of BESS. The total electricity price and reliability indices for both grid-connected and islanded MGs are calculated, with and without considering the optimal size of the BESS. To determine the optimized size, a firefly optimization algorithm is used as an efficient meta-heuristic approach. The total cost, which includes the cost of generation units, exchanged electricity cost, and BESS investment cost, is considered as the fitness function for the problem. The results of the study show that utilizing BESS in grid-connected MGs without limitations on exchanged power with the main grid may not be economically beneficial and may not significantly improve reliability. However, it can improve the expected energy not supplied (EENS) of both islanded and grid-connected MGs with power exchange limitations by up to 10.2% and 35.77%, respectively. Additionally, life cycle is an important factor in determining the type of BESS for islanded MGs. Other Information Published in: IEEE Access License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1109/access.2023.3288427